2003
DOI: 10.1016/s0886-3350(02)01695-4
|View full text |Cite
|
Sign up to set email alerts
|

Exodeviation following monocular myopic regression after laser in situ keratomileusis

Abstract: We report a 44-year-old woman with intermittent left exotropia of 35 prism diopters at distance who initially exhibited alignment of both eyes after bilateral laser in situ keratomileusis (LASIK). The exophoria was not preserved due to myopic regression in the dominant eye. An uneventful LASIK treatment was performed to correct -11.00 -0.50 x 130 in the right eye and -13.50 -1.50 x 145 in the left eye. The aim was to achieve emmetropia in both eyes. Although an examination revealed exophoria at near and distan… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
9
0

Year Published

2005
2005
2017
2017

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(10 citation statements)
references
References 8 publications
1
9
0
Order By: Relevance
“…If strabismus is present with refractive error, refractive surgery should normally be performed first because it may have an effect on the strabismus angle. Some time should pass to allow for regression of the refractive effect before the strabismus is assessed for realignment surgery 21 . If strabismus surgery is performed first, the so‐called fornix approach is better because it enables normal microkeratome suction.…”
Section: Refractive Surgery In Patients With Strabismusmentioning
confidence: 99%
“…If strabismus is present with refractive error, refractive surgery should normally be performed first because it may have an effect on the strabismus angle. Some time should pass to allow for regression of the refractive effect before the strabismus is assessed for realignment surgery 21 . If strabismus surgery is performed first, the so‐called fornix approach is better because it enables normal microkeratome suction.…”
Section: Refractive Surgery In Patients With Strabismusmentioning
confidence: 99%
“…Decompensation of exodeviations have also been reported after refractive surgery, however, and can result in secondary strabismus surgery. 10,11 We are aware of only 1 report in which exotropia improved after LASIK. In that report, the proposed mechanism was resolution of anisometropia, with subsequent improvement of binocular function.…”
Section: Discussionmentioning
confidence: 99%
“…Some studies have described cases with postoperative diplopia retrospectively, or included a pre-selected population with various manifest strabismus. [7][8][9][10][11][12][13][14][15]18 Moreover, the impact of myopic refractive surgery on exodeviation has been reported to vary among reports. 2,4,6,18 We identified that corneal refractive surgery for low to moderate myopia in general did not appear to have an impact on ocular alignment.…”
Section: Discussionmentioning
confidence: 99%
“…[2][3][4][5][6] Conversely, although 10-year follow-ups have demonstrated that the technique is safe and predictable, 1 refractive surgery can cause strabismus and binocular diplopia. 2,[7][8][9][10][11][12][13][14][15] Patients with preexisting strabismus or anisometropiacausing aniseikonia, and those hoping to achieve monovision are at higher risk for postoperative strabismus and diplopia. 7 Therefore, refractive surgery might be a means of treatment for strabismus and a cause of strabismus.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation